2023
DOI: 10.3126/njdvl.v21i1.47643
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Clinical Efficacy of Topical Application of Virgin Coconut Oil and 1% Clotrimazole Cream as an Adjuvant to Systemic Antifungal in Chronic Dermatophytoses: A Randomized Controlled Trial

Abstract: Introduction: Dermatophyte infections have become a common entity with a prevalence ranging from 36.6-78.4%. Majority of the patients are from low socioeconomic background who favour topical treatment. High treatment costs of antifungal medication and consequent poor compliance have given rise to the need of an effective and economical topical preparation.   Objectives: To compare efficacy of topical 1% clotrimazole versus virgin coconut oil application as an adjuvant to systemic antifungals in dermatophytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Jones et al 9 There has been dearth of studies where moisturisers use was compared with topical antifungal agents. However, there has been a study where topical antifungal was compared with virgin coconut oil by Chawla et al 10 as an adjuvant to systemic antifungal in chronic dermatophytosis. It was found that both have comparable efficacy and tolerability.…”
Section: Chronic and Recurrent Dermatophytosis Has Emerged As A Majormentioning
confidence: 99%
“…Jones et al 9 There has been dearth of studies where moisturisers use was compared with topical antifungal agents. However, there has been a study where topical antifungal was compared with virgin coconut oil by Chawla et al 10 as an adjuvant to systemic antifungal in chronic dermatophytosis. It was found that both have comparable efficacy and tolerability.…”
Section: Chronic and Recurrent Dermatophytosis Has Emerged As A Majormentioning
confidence: 99%